Placental Vimentin Expression in Preeclampsia and Gestational Diabetes Mellitus - Fırat Asir; Suleyman Cemil Oglak; Tugcan Korak; Fatih Tas; Mehmet Yilmaz; Fikri Erdemci; Firat Sahin; Hayat Ayaz; Emine Zeynep Yilmaz; Gokhan Bolluk (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: This study investigated vimentin expression in placentas of patients with preeclampsia and gestational diabetes mellitus (GDM).